2002
DOI: 10.2209/tdcpublication.43.75
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Mass and Degree of Deacetylation of Chitosan on Adsorption of Streptococcus sobrinus 6715 to Saliva Treated Hydroxyapatite.

Abstract: We evaluated the influence of molecular mass and degree of deacetylation of chitosan on the adsorption of Streptococcus sobrinus 6715 to saliva-treated hydroxyapatite (S-HA) by measuring the optical density of the bacterial cell suspensions released from saliva-treated hydroxyapatite. Twenty-five chitosan samples with different molecular masses (0.8-6 kDa) and degrees of deacetylation (10-95%) were prepared for the study. We found that the inhibition of adsorption of S. sobrinus 6715 to S-HA correlated positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…The positive charge of chitosan‐treated pellicles explains the decreased viability of S. sanguinis attached to saliva‐coated enamel treated with chitosan (8). The increased hydrophobicity of salivary pellicles after chitosan adsorption explains the reduced adhesion of Streptococcus sobrinus to saliva‐coated hydroxyapatite disks, which was minimal for chitosans with a molecular weight of 5–6 kDa and a degree of acetylation of 50–60% (10). Also in vivo , low‐molecular‐weight chitosans inhibited the initial adhesion of oral bacteria to human tooth surfaces at a level comparable to that of a 50 mg l −1 (50 p.p.m.)…”
mentioning
confidence: 99%
“…The positive charge of chitosan‐treated pellicles explains the decreased viability of S. sanguinis attached to saliva‐coated enamel treated with chitosan (8). The increased hydrophobicity of salivary pellicles after chitosan adsorption explains the reduced adhesion of Streptococcus sobrinus to saliva‐coated hydroxyapatite disks, which was minimal for chitosans with a molecular weight of 5–6 kDa and a degree of acetylation of 50–60% (10). Also in vivo , low‐molecular‐weight chitosans inhibited the initial adhesion of oral bacteria to human tooth surfaces at a level comparable to that of a 50 mg l −1 (50 p.p.m.)…”
mentioning
confidence: 99%
“…In fact, the polycationic nature of CS, with active amino and hydroxyl functional groups, permits good adhesion to salivary pellicles and creates positive charges that interact with microbial cell surfaces provoking loss of microbial cell barrier function [410]. Sano et al demonstrated the effect of increased hydrophobicity of salivary pellicles after CS adsorption and the obtained reduced adhesion of Streptococcus sobrinus to saliva coated HA disks [411]. They also found that low molecular weight CS inhibits the initial adhesion of oral bacteria to human tooth surfaces at a level comparable to that of a 50 ppm chlorhexidine solution [412].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%
“…The formulation of chitosan with a drug may alter the pharmacokinetic and biodistribution profiles, and for pharmaceutical applications it is necessary to take in account the route of administration, its concentration, contact time and cell types that enter in contact with chitosan or chitosan complexes [58][59][60][61][62][63]. In Table 4 are listed some biological and toxicological properties of chitosan in several biological systems [64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Biological Propertiesmentioning
confidence: 99%